2014
DOI: 10.1038/ncomms5317
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular redox protein MICAL-1 regulates the development of hippocampal mossy fibre connections

Abstract: Mical is a reduction-oxidation (redox) enzyme that functions as an unusual F-actin disassembly factor during Drosophila development. Although three Molecule interacting with CasL (MICAL) proteins exist in vertebrate species, their mechanism of action remains poorly defined and their role in vivo unknown. Here, we report that vertebrate MICAL-1 regulates the targeting of secretory vesicles containing immunoglobulin superfamily cell adhesion molecules (IgCAMs) to the neuronal growth cone membrane through its abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(89 citation statements)
references
References 70 publications
(118 reference statements)
1
86
0
Order By: Relevance
“…For example, Drosophila MICAL is identified as an essential for neuronal growth by interactions with the cytoplasmic region of plexin and activating plexin‐ and semaphorin‐mediated axonal signalling 20. Recent studies also reported that MICAL1 promoted the development of hippocampal mossy fibre connections through its ability to control actin cytoskeleton rearrangement 21. The notion that cell cytoskeleton rearrangement contributes to cell proliferation has been confirmed by many research groups15; however, up to now, no study yet addressed the function of MICAL1 in the human cancer cell proliferation process.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Drosophila MICAL is identified as an essential for neuronal growth by interactions with the cytoplasmic region of plexin and activating plexin‐ and semaphorin‐mediated axonal signalling 20. Recent studies also reported that MICAL1 promoted the development of hippocampal mossy fibre connections through its ability to control actin cytoskeleton rearrangement 21. The notion that cell cytoskeleton rearrangement contributes to cell proliferation has been confirmed by many research groups15; however, up to now, no study yet addressed the function of MICAL1 in the human cancer cell proliferation process.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that Mical1 is a negative regulator of apoptosis, wherein inhibition of Mical1 induced rapid NDR-dependent (nuclear Dbf2-related kinase) apoptosis in melanoma cells (39). Another report demonstrated that Mical1, through redox regulation of actin cytoskeleton, controls the intracellular distribution of secretory vesicles that, in turn, regulates growth cone membrane targeting of the cell adhesion molecule (IgCAMs) in neurons (67). Therefore, it appears that Mical1 controls the development of lamina-restricted hippocampal moss fiber connection.…”
Section: Stereospecific Regulation Of Meto By Selenoprotein Msrb1mentioning
confidence: 99%
“…Numerous mossy fiber terminals were seen scattered within the pyramidal cell layer in Chl1 ¡/¡ mice, suggesting that the terminals were formed not only on proximal dendrites of the pyramidal cells, but also on the cell bodies. 26,27,36 Interestingly, NCAM-deficient animals also have demonstrated similar abnormal projections of mossy fibers in the hippocampus. 25 However, we did not observe an increased mossy fiber invasion into the SP of Cntn6 ¡/¡ mice, but rather an increase in length and size of mossy fiber projections in the SPB.…”
Section: Discussionmentioning
confidence: 99%
“…The fasciculation of efferents of this system is sensitive to alterations in axon guidance molecules and CAMs. 26,27,[34][35][36] In the hippocampus of P14 and adult mice, there was low Cntn6 mRNA expression in the pyramidal neurons of CA1 and CA3, in the granular neurons of the DG and in the dispersed cell bodies inside the hilus of the DG (Fig. 1C).…”
Section: Differential Spatiotemporal Expression Of Cntn6 In the Brainmentioning
confidence: 99%